Jaminan Fidusia dan Potensi Meningkatkan Laju Ekonomi - Widhi Handoko (Magister Kenotariatan, Universitas Jambi, 2019)
Launch of online fiduciary reform is a concrete step that will contribute positively to the strengthening of security system moving objects Indonesia. The low compliance with registration and revocation of registration of fiduciary requires supporting policies that can support the compliance. Fiduciary will be optimal if the markets take full advantage of fiduciary guarantee registration system as a tool for business decision-making. Need an integrated policy between the authorities in the legal sector with the authorities in the financial sector/financing to support the implementation and utilization of the fiduciary